Effect of Return on Assets (ROA) and Debt to Equity (DER) on Firm Value: Study of One of The Selected Bank Companies on the IDX - Amalia Anggraeni Puspitarini; Bulan Tati Fitria (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
The motivation behind this study stems from the occurrence of issues within a specific bank company listed on the IDX. These issues are reflected in the suboptimal performance of Return on Assets (ROA) and Debt to Equity (DER), which in turn impact the bank company's overall firm value on the IDX. This study aims to assess the extent to which Return on Assets (ROA) and Debt to Equity (DER) impact the perceived firm value of a chosen bank company listed on the IDX. The present study employs a quantitative research methodology, precisely a Descriptive and Verification approach. The data for this study is obtained from the financial reports of a chosen bank company listed on the IDX. The data collection spans from 2016 to 2021, encompassing quarterly reports issued by the company. The study utilizes financial report data from a selected bank company listed on the IDX. The data is processed using SPSS 25 software. This research's findings demonstrate a statistically significant positive relationship between Return on Assets (ROA) and Firm Value. This result is evidenced by a Sig value of 0.048, less than the conventional significance level of 0.05. Additionally, the T-count value of 2.101 exceeds the critical value, further supporting the significance of this relationship. The table displaying the 2.07961 (2) coefficient for the Debt to Equity (DER) ratio indicates a statistically significant positive impact on Firm Value. This result is evidenced by the Sig value of 0.001, which is less than the conventional significance level of 0.05. Additionally, the T-count value of -4.043, which is greater than the critical value, further supports the significance of this relationship. The study conducted on the relationship between Return on Assets (ROA) and Debt to Equity (DER) on Firm Value found that a coefficient of 2.10982 (p < 0.05) indicates a direct effect of 66.7%. However, it is essential to note that the remaining 33.7% of Firm Value is influenced by other variables not examined in this study.